PEMBUATAN TERMOPLASTIK RAMAH LINGKUNGAN BERBASIS KHITOSAN MELALUI PENAMBAHAN REFINED BLEACHED AND DEODORIZED PALM OIL (RBDPO) DAN GLISEROL SEBAGAI PEMLASTIS - M. Hasan (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2012)
Chitosan, a product of chitin deacetylation, has been used for various purposes in various fields of agriculture, food, biomedical, biotechnology, and pharmaceuticals. The use of chitosan in a pure state is limited by its poorly soluble in various solvents other than in aqueous weak acids. Moreover, chitosan films are brittle and fragile that it is difficult to use in the form of films for various applications. Long-term goal of this research is to obtain chitosan which is elastic by the addition of plasticizer. The specific target of this research is to obtain information about the effect of adding RBDPO and glycerol as plasticizer on the characteristics of the mechanical properties of chitosan. The research method was carried out in the laboratory experiments. Design research is conducted on a wide variety of compositions blending chitosan and plasticizer of RBDPO and glycerol on the mechanical properties including tensile strength and elongation. The relsulted blended sample is cast in the form of thin films and characterized by tensile strength test. The test results showed that the mechanical properties of tensile strength reaches optimum conditions where the plasticizer content of 30%, while the extension increases with increasing of plasticizer content.